A patient with a novel homozygous missense mutation in FTO and concomitant nonsense mutation in CETP. - Çağlayan, Ahmet O; Tuysuz, Beyhan; Coşkun, Süleyman; Quon, Jennifer; Harmancı, Akdes S; Baranoski, Jacob F; Baran, Burçin; Erson-Omay, E Zeynep; Henegariu, Octavian; Mane, Shrikant M; Bilguvar, Kaya; Yasuno, Katsuhito; et al. (J Hum Genet, 2016)
The fat mass and obesity associated (FTO) gene has previously been associated with a variety of diseases and conditions, notably obesity, acute coronary syndrome and metabolic syndrome. Reports describing mutations in FTO as well as in FTO animal models have further demonstrated a role for FTO in the development of the brain and other organs. Here, we describe a patient born of consanguineous union who presented with microcephaly, developmental delay, behavioral abnormalities, dysmorphic facial features, hypotonia and other various phenotypic abnormalities. Whole-exome sequencing revealed a novel homozygous missense mutation in FTO and a nonsense mutation in the cholesteryl ester transfer protein (CETP). Exome copy number variation analysis revealed no disease-causing large duplications or deletions within coding regions. Patient's, her parents' and non-related control' fibroblasts were analyzed for morphologic defects, abnormal proliferation, apoptosis and transcriptome profile. We have shown that FTO is located in the nucleus of cells from each tested sample. Western blot analysis demonstrated no changes in patient FTO. Quantitative (qPCR) analysis revealed slightly decreased levels of FTO expression in patient cells compared with controls. No morphological or proliferation differences between the patient and control fibroblasts were observed. There is still much to be learned about the molecular mechanisms by which mutations in FTO contribute to such severe phenotypes.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Apoptosis; Biopsy; Child, Preschool; Cholesterol Ester Transfer Proteins; Computational Biology; Consanguinity; DNA Copy Number Variations; DNA Mutational Analysis; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Association Studies; Genotype; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Mutation, Missense; Phenotype; Transcriptome

Recessive loss of function of the neuronal ubiquitin hydrolase UCHL1 leads to early-onset progressive neurodegeneration. - Bilguvar, Kaya; Tyagi, Navneet K; Ozkara, Cigdem; Tuysuz, Beyhan; Bakircioglu, Mehmet; Choi, Murim; Delil, Sakir; Çağlayan, Ahmet O; Baranoski, Jacob F; Erturk, Ozdem; Yalcinkaya, Cengiz; Karacorlu, Murat; et al. (Proc Natl Acad Sci U S A, 2013)
Ubiquitin C-terminal hydrolase-L1 (UCHL1), a neuron-specific de-ubiquitinating enzyme, is one of the most abundant proteins in the brain. We describe three siblings from a consanguineous union with a previously unreported early-onset progressive neurodegenerative syndrome featuring childhood onset blindness, cerebellar ataxia, nystagmus, dorsal column dysfuction, and spasticity with upper motor neuron dysfunction. Through homozygosity mapping of the affected individuals followed by whole-exome sequencing of the index case, we identified a previously undescribed homozygous missense mutation within the ubiquitin binding domain of UCHL1 (UCHL1(GLU7ALA)), shared by all affected subjects. As demonstrated by isothermal titration calorimetry, purified UCHL1(GLU7ALA), compared with WT, exhibited at least sevenfold reduced affinity for ubiquitin. In vitro, the mutation led to a near complete loss of UCHL1 hydrolase activity. The GLU7ALA variant is predicted to interfere with the substrate binding by restricting the proper positioning of the substrate for tunneling underneath the cross-over loop spanning the catalytic cleft of UCHL1. This interference with substrate binding, combined with near complete loss of hydrolase activity, resulted in a >100-fold reduction in the efficiency of UCHL1(GLU7ALA) relative to WT. These findings demonstrate a broad requirement of UCHL1 in the maintenance of the nervous system.
Keywords: Adult; Age of Onset; Amino Acid Sequence; Base Sequence; Child, Preschool; Exome; Female; Genes, Recessive; Homozygote; Humans; Hydrolysis; Male; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Nerve Degeneration; Neurons; Pedigree; Protein Binding; Sequence Analysis, DNA; Substrate Specificity; Syndrome; Thermodynamics; Ubiquitin; Ubiquitin Thiolesterase